Non-linear programming : a basic introduction - Shah, Nita H.; Mishra, Poonam Prakash (Boca Raton, FL : CRC Press, an imprint of Taylor & Francis Group, LLC, 2021)
"This book is for beginners who are struggling to understand and optimize non-linear problems. The content will help readers gain an understanding and learn how to formulate real-world problems and will also give insight to many researchers for their future prospects. It proposes a mind map for conceptual understanding and includes sufficient solved examples for reader comprehension. The theory is explained in a lucid way. The variety of examples are framed to raise the thinking level of the reader and the formulation of real-world problems are included in the last chapter along with applications. The book is self-explanatory, well synchronized and written for undergraduate, post graduate and research scholars"--
Try Yourself -- 4 Applications of Non-Linear Programming -- 4.1 Basics of Formulation -- 4.2 Examples of NLP Formulation -- Example 1: Profit Maximization -- Production Problem -- Example 2: Cost Minimization -- Optimum Designing Problem -- Example 3: Cost Minimization -- Electrical Engineering -- Example 4: Design of a Small Heat Exchanger Network -- Chemical Engineering -- Example 5: Real-Time Optimization of a Distillation Column -- Petroleum Engineering -- 4.3 Solving NLP through MATLAB Inbuilt Functions -- 4.4 Choice of Method -- Try Yourself -- Bibliography -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Nonlinear programming; MATHEMATICS / Applied; TECHNOLOGY / Operations Research; BUSINESS & ECONOMICS / Operations Research